Accuracy of polymerase chain reaction-restriction fragment length polymorphism for RET rs2435357 genotyping as Hirschsprung risk - Gunadi; Dwihantoro, Andi; Iskandar, Kristy; Makhmudi, Akhmad; Rochadi (The Journal of surgical research, 2016)
Recently, the common RET rs2435357 variant has been shown to be strongly related to Hirschsprung disease (HSCR) in the Indonesian population. This association study was conducted in developed areas using high-throughput TaqMan polymerase chain reaction (PCR) assay. Although the TaqMan method is less time-consuming, it requires a special more expensive PCR machine and a highly skilled analyst. In this study, we analyzed the usefulness of the PCR-restriction fragment length polymorphism (RFLP) method for genotyping RET rs2435357 polymorphism in Indonesian HSCR patients given the limitation of resource allocation for more expensive technologies. We compared our previous genotyping results of RET rs2435357 in 53 HSCR patients and 86 controls using the TaqMan PCR assay with the PCR-RFLP technique. Furthermore, we included an additional 40 HSCR patients and 50 controls and subsequently genotyped all subjects using the PCR-RFLP method. Compared with our previous genotyping data of RET rs2435357 using the TaqMan PCR assay, the PCR-RFLP method indicated 100% concordant results. The overall accuracy of the PCR-RFLP for RET rs2435357 genotyping was 100%. In addition, case-control analysis demonstrated that RET rs2435357 is significantly correlated with HSCR (P = 2.2 × 10−13) with an odds ratio of 5.1 (95% confidence interval = 3.2-8.1). The transmission disequilibrium test revealed that risk allele (T) at rs2435357 is significantly overtransmitted to probands at a transmission rate (τ) of 0.87 (P = 1.5 × 10−6). The PCR-RFLP method is reliable and affordable for genotyping of RET rs2435357 polymorphism in developing countries. Our results strengthen the proof that the RET rs2435357 variant is a genetic risk for HSCR in Indonesia.